2013
DOI: 10.1001/jamapediatrics.2013.13
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on Clinical Outcomes in Hospitalized Children

Abstract: Importance Obesity is prevalent among hospitalized children. Knowledge of the relationship between obesity and outcomes in hospitalized children will enhance nutrition assessment and provide opportunities for interventions. Objective To systematically review the existing literature concerning the impact of obesity on clinical outcomes in hospitalized children. Evidence Acquisition PubMed, Web of Science, and EMBASE databases were searched for studies of hospitalized children aged 2 to 18 years with identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 53 publications
(106 reference statements)
0
46
0
5
Order By: Relevance
“…In children admitted for status asthmaticus, obesity was a significant predictor of PICU stay [36]. Pediatric cohorts with critical illness, cancer, solid organ and stem cell transplantation have a mortality association with obesity [37]. In our current study, children who were obese or underweight had significantly longer hospital stays but their odds of acquiring an infection were not higher.…”
Section: Discussionmentioning
confidence: 53%
“…In children admitted for status asthmaticus, obesity was a significant predictor of PICU stay [36]. Pediatric cohorts with critical illness, cancer, solid organ and stem cell transplantation have a mortality association with obesity [37]. In our current study, children who were obese or underweight had significantly longer hospital stays but their odds of acquiring an infection were not higher.…”
Section: Discussionmentioning
confidence: 53%
“…[1][2][3] Recent studies have demonstrated worsened pediatric in-hospital outcomes, including mortality and increased resource utilization, for children with obesity across a range of diagnoses. [4][5][6][7][8][9][10] Although the mechanisms driving the association between obesity and in-hospital outcomes are not fully known, for asthma it is believed that adipocytes expressing inflammatory markers create a low level of systemic inflammation, thereby increasing the severity of allergic-type illnesses and decreasing the response to anti-inflammatory medications, such as steroids. [11][12][13][14][15][16][17][18] The relationship of obesity and in-hospital asthma outcomes is of particular interest because status asthmaticus is the most common reason for admission in children aged 3 to 12 years, accounting for approximately 150,000 admissions (7.4% of all hospitalizations for children and adolescents) and $835 million in hospital costs annually.…”
Section: Resultsmentioning
confidence: 99%
“…En esta clasificación aparecen diagnósticos más específicos como los desnutridos crónicos activos o descompensados que corresponde a aquellos niños que tienen compromiso de talla pero que además su estado nutricional es deficiente en peso para esa talla como también están los niños desnutridos crónicos sobre compensados, es decir, el aporte de energía está siendo excesivo en el manejo de su recuperación nutricional. Por lo cual realizar un correcto diagnóstico nutricional nos orienta los requerimientos de energía de un niño, sobretodo cuando existe evidencia que tanto malnutrición por déficit como por exceso otorga mayor morbilidad 16,18 . La CAI no es específica de niños con CC, por lo que esta clasificación es útil en niños que cursen por distintas causas con compromiso de talla.…”
Section: Discussionunclassified